Evaluation of toxicity and antibacterial activities of Andrographis paniculata herbal mouthwash against oral pathogens - Anis Amiera Muhamad Alojid,; Tuan Noorkorina Tuan Kub,; Halijah Miran,; Suharni Mohamad,; Tuan Nadrah Naim Tuan Ismail,; Mohamad Ezany Yusoff,; Rosmaniza Abdullah,; Siti Asma’ Hassan,; Zeti Norfidiyati Salmuna,; Nusaadatun Nisak Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Andrographis paniculata (AP) is an ancient herb known for its medicinal and therapeutic values. In this study, we aimed to evaluate the antibacterial activity and cytotoxicity of AP herbal mouthwash. Aqueous extract of AP was used to prepare the herbal mouthwash. The product was tested against selected oral pathogens namely Actinomyeces viscosus, Staphylococcus aureus, Streptococcus mutans, Streptococcus sobrinus, and Porphyromonas gingivalis for its antibacterial activity using the agar well diffusion method. Toxicity analysis was carried out and subjected to cytotoxicity screening using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, in vivo study using brine shrimp lethality bioassay, and detection of heavy metals using atomic absorption spectroscopy (AAS). Five AP herbal mouthwash concentrations (62.5, 125, 250, 500, 1000 mg/mL) were developed. AP herbal mouthwash exhibited the strongest antibacterial activity against A. viscosus. AP herbal mouthwash (125 to 1000 mg/mL) showed inhibition against P. gingivalis, S. mutans and S. sobrinus, except for S. aureus which did not reflect any sign of antibacterial activity. In brine shrimp lethality bioassay, AP herbal mouthwash has LC50 3255.064 μg/mL. In vitro cytotoxic evaluation was done on L929 mouse fibroblast cell lines using MTT assay with IC50 43.55 mg/mL denotes the mouthwash is non-toxic. Heavy metals content in AP herbal mouthwash falls within the permissible range of plumbum (2.50 ppm) followed by arsenic (1.875 ppm), mercury (0.15 ppm), and cadmium (0.06 ppm). Thus, verifying AP herbal mouthwash is effective in common oral pathogens and has a non-toxic effect.